Intersubjectivity as an analytical concept to study human-animal interaction in historical context: street dogs in Late Ottoman period - Taşdizen, Burak; Yetiş, Erman Örsan; Bakırlıoğlu, Yekta (Frontiers in Sociology, 2024)
Human knowledge pertaining to human-animal interaction is constructed by the human author, albeit the presence of animal subjects. Such a human lens is pronounced when studying human-animal interactions across history, whose nonhuman animal subjects are not only absent, and therefore eliminating the possibility of conducting empirical studies in situ, but also their experiences are filtered by the interpretative lens of human authors of extant historical accounts as well as contemporary human analysts who interpret these accounts. This article draws upon such epistemological limitations of understanding nonhuman animal presence in historical accounts and offers human-animal intersubjectivity as an analytical concept, involving generative iterability and indistinctive boundaries that emphasise intersubjective openness and relationality, to trace and disclose the continuity of human-animal co-existence. The article’s historical scope is the Late Ottoman period characterised by a sense of temporal and spatial disorientation and reorientation for humans as well as street dogs during its modernisation processes.